PASTORAL CARE BAGI JEMAAT DEWASA MUDA DENGAN GAMOPHOBIA MENUJU PERNIKAHAN KRISTEN - Dian Cyntiawati; Yanto Paulus Hermanto; Jessica Elizabeth Abraham (Manna Rafflesia, 2023)
Today some young adults decide not to marry. Various reasons were put forward, including fear of being committed to their partner ‒how to interact with their partner's family – not to mention the matter of heredity. These things make young adults experience gamophobia and no longer care about married life. Gamophobia, if not overcome, will result in both physical and psychological disturbances to the young adults themselves. It can even impact the people around him, especially those closest to him. This study used a qualitative method by observing the phenomena experienced by young adults, then the researchers conducted interviews with informants who participated gamophobia. A study analysis was carried out through the literature and then the results were explained descriptively. It was found that a lack of understanding of marriage made young adults avoid it. Pastoral care in the youth community and religious counseling services play an essential role in helping young adults with gamophobia experience a full recovery. It is hoped that through these services, young adults will overcome fear and be ready to enter the marriage ladder. In the end, the church will thrive; and become a witness to the world through the life of its congregation.